Исторические аспекты возникновения магнитно-импульсного притяжения тонкостенных листовых металлов - Батыгин, Юрий Викторович; Гнатов, Андрей Викторович (НТУ "ХПИ", 2011)
В статье раскрыты истоки возникновения нового направления в МИОМ, как магнитно-импульсное притяжение тонкостенных листовых металлов. Проведен анализ предложений в патенте Г. Фюрта и показана возможность их практической реализации. Раскрыта идея мспользования двух источников электромагнитного поля в практике магнитно-импульсного притяжения листовых металлов

In the article, origination of a new direction in Electrical Magnetic Metal Forming such as magnetic pulse attraction of thinwall sheet metals is analyzed. Patent No. 3,196,649 (H.Furth, 1965) claim is commented. Practical realization of the suggestion is shown impossible. The idea of utilization of two sources of (high-frequency and low-frequency) electromagnetic field for sheet metals magnetic pulse attraction is analyzed
Historical aspects of thin-wall sheet metals magnetic-pulse attraction technology origination
Keywords: электромагнитное поле; рихтовка; импульсные поля; силы притяжения; electrical magnetic metal forming; patent; coil; intensity of a magnetic field; current